Compare the effect of amniotomy and oxytocin infusion in duration of labour - Jyothi, Katta; Shakunthala, Senadhipathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Labour is a unique experience in a women’s life, it is a physiological but painful event. It is a dynamic and continuous process which cumulates in the birth of a healthy baby followed by expulsion of the placenta and the membranes. The objective of this study was to determine the effectiveness of amniotomy and oxytocin in terms of duration of labour, mode of delivery and maternal and fetal outcome. Methods: A non-randomized comparative study of accelerating effect of oxytocin and amniotomy has been studied, in the age group of 19-30 years, who are admitted in obstetric ward 200 primigravidae were studied out of which 100 belongs to control group and 100 study group. Results: In the study series 93 cases had labour lasting less than 4 hours when compared to only. The mean total duration of labour is reduced in study group with a difference of 204 minutes. Quantity and duration of blood loss is significantly less in study group when compared to control group. There was no significant difference in terms of mode of delivery, maternal and foetal outcome between the two groups. Conclusions: Oxytocin infusion combined with amniotomy is safe and effective in accelerating the first and second stage of labour in apparently normal cases. No statistically significant adverse effects were noted with oxytocin infusion and amniotomy.